TINJAUAN HUKUM TERHADAP PENYELESAIAN PERKARA PIDANA ANAK PADA TINGKAT PENYIDIKAN MELALUI DIVERSI DI WILAYAH KEPOLISIAN RESORT TOLITOLI - Rista Amanda (LEGAL OPINION, 2024)
The purpose of this research: To find out the settlement of juvenile criminal cases through diversion at the investigation level at the Tolitoli Resort Police. To find out the obstacles in the settlement of juvenile criminal cases through diversion at the investigation level at the Tolitoli Resort Police. The type of research used in writing this thesis is Empirical Law. The settlement of juvenile criminal cases through diversion, especially at the investigation level by investigators of the PPA Unit of the Tolitoli Police Criminal Investigation Unit, has taken place in accordance with the rules based on Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. Factors inhibiting the settlement of juvenile criminal cases at the investigation level through diversion are economic factors (compensation from the perpetrator and family) and family factors of the victim's family. Tujuan dalam penelitian ini: Untuk mengetahui penyelesaian perkara pidana anak melalui diversi pada tingkat penyidikan di Kepolisian Resort Tolitoli. Untuk mengetahui hambatan dalam penyelesaian perkara pidana anak melalui diversi pada tingkat penyidikan di Kepolisian Resort Tolitoli. Tipe penelitian yang digunakan dalam penulisan skripsi ini adalah Hukum Empiris. Penyelesaian perkara pidana anak melalui diversi khususnya di tingkat penyidikan oleh penyidik Unit PPA Sat Reskrim Polres Tolitoli telah berlangsung sesuai dengan aturan berdasarkan Undang-undang Nomor 11 Tahun 2012 tentang Sistem Peradilan Pidana Anak. Faktor penghambat penyelesaian perkara pidana anak pada tingkat penyidikan melalui diversi adalah faktor ekonomi (ganti rugi dari pihak pelaku dan keluarga) dan faktor keluarga keluarga korban.